A case study: Brown-green infrastructure in a semi-arid - Schmidbauer, Gaby Bianca (School of Architecture, Planning and Geomatics, 2018)
“Green infrastructure is defined as an interconnected network of “green” space that conserves natural ecosystem values and functions and provides related benefits to both human and non-human (Fauna & Flora) population. Green Infrastructure is therefore a new ecological (framework) model needed for considering spatial, environmental, social and economic sustainability in a bigger strategic context—in short it is an essential natural life sustaining system for our nation. The green infrastructure model provides a contemporary and innovative way to address this strategic absence in the urban environment. Despite different definition of what constitute green infrastructure, most theorists agree that it comprises 3 things: connectivity, multi-functionality, and “green”. River corridors are natural ecosystems considered as “Green” Infrastructure, which provide an interconnected network of “green” open spaces in cities. In terms of connectivity, Windhoek, Namibia, has three major ecological corridors along the Klein Windhoek, Gammams and Arebbusch rivers, connecting suburbs, the city and two major dams known as Goreangab dam, North-West and Avis dam, South East of Windhoek. The rivers are ephemeral; it creates a contrast between a dominant dry season to a relative “wet” season i.e. due to water flow during a specific time of the year. Over 200 hectares of river course space during both peak and non-peak events is underutilised. These existing open spaces are left unused, polluted and poorly managed reducing their potential for “multi-functionality”. Most critically however, Windhoek is a semi-arid landscape and not necessarily “green”. This begs the question: Does “green” infrastructure have to be green? In semi-arid regions, many green infrastructure practices may not be “green” at all. 3 Windhoek, will therefore be used as a case study to test how green infrastructure might function in a different way when it is not entirely green, which is a key part of green infrastructure. Would “brown-green” infrastructure be a better description for this context?